Harapan dan Penilaian Industri Konstruksi terhadap Ketrampilan Lulusan Teknik Sipil - Albani Musyafa (Unisia, 2009)
This research proposes to explore the quality of graduates of higher education in civilengineering in Australia. The result of the research can be used to help civil engineeringeducation providers to apply a strategy to improve the quality of their graduates. The studyuses primary data from the personal of construction industry, the data of which are analyzedstatistically. This study reveals about the evaluation of the skill of civil engineeringgraduates by construction industry; the expectation of construction industry toward theskill which has to be mastered by graduates of civil engineering; and the gap between theevaluation and the expectation.Keywords: construction industry, skill of graduates, quality of graduates, civil engineering.